Application of Stem Cell Therapy During the Treatment of HIV/AIDS and Duchenne Muscular Dystrophy - Chitena, Lorraine; Masisi, Keletso; Masisi, Kabo; Kwape, Tebogo E.; Gaobotse, Goabaone (Current Stem Cell Research & Therapy, 2022)
Treating diseases such as Muscular Dystrophy (MD) and HIV/AIDS pose several challenges to the rapidly evolving field of regenerative medicine. Previously, stem cell therapy has been said to affect the clinical courses of HIV/AIDS and MD, but, in practice, eradication or control of these diseases was not achievable. The introduction of gene editing into stem cell therapy has stimulated HIV/AIDS and MD cell therapy research studies substantially. Here, we review current methods of treating HIV/AIDS and MD using stem cell therapy. This review also details the use of different types of cells and methods in cell therapy and the modeling of new cell-based therapies to treat Duchenne muscular dystrophy. We speculate that the effective use of stem cell therapy in conjunction with other treatment therapies , such as steroids and rehabilitation , could improve livelihood.
Keywords: muscular dystrophy